Characterization of Calcium Oxalate Biominerals in Pereskia Species (Cactaceae) - Monje, Paula V. (2009)
Calcium oxalate druses were isolated from the stems and leaves of six Pereskioideae family members and investigated by infrared spectroscopy, showing that in all samples the biomineral was present in the form of whewellite, CaC2O4 · H2O. As Pereskia is thought to represent the “ancestral” condition of the leafl ess stem-succulent cacti, these results suggest that the biomineralization of calcium oxalate in Cactaceae represents a primitive characteristic of the group and also support a close genetic relationship between Pereskia and Opuntia.